2014
DOI: 10.1186/1471-2458-14-12
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviour, sexually transmitted infections and attitudes to chlamydia testing among a unique national sample of young Australians: baseline data from a randomised controlled trial

Abstract: BackgroundChlamydia infection is the most common notifiable sexually transmitted infection (STI) in Australia and mostly affects young people (15 – 25 years). This paper presents baseline data from a randomised controlled trial that aimed to increase chlamydia testing among sexually active young people. The objectives were to identify associations between sexual behaviour, substance use and STI history and explore attitudes to chlamydia testing.MethodsThis study was conducted in cyberspace. Study recruitment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
(22 reference statements)
2
13
2
2
Order By: Relevance
“…21,24,25 This concurs with our study, in particular the use of ecstasy and injecting drugs in the last 12 months were important factors associated with a self-reported STI diagnosis, as was a pattern of risky alcohol consumption. These data underscore the need for more comprehensive approaches to address drug and alcohol use among young Aboriginal people.…”
Section: Discussionsupporting
confidence: 90%
“…21,24,25 This concurs with our study, in particular the use of ecstasy and injecting drugs in the last 12 months were important factors associated with a self-reported STI diagnosis, as was a pattern of risky alcohol consumption. These data underscore the need for more comprehensive approaches to address drug and alcohol use among young Aboriginal people.…”
Section: Discussionsupporting
confidence: 90%
“…The C. trachomatis prevalence rates found in this study are lower than in other Australian studies with similar samples in terms of age and gender (Kang et al 2014). The protective factors noted above may account for some of this difference.…”
Section: Comparability Of Sexual Behaviour In the Adf With The Austracontrasting
confidence: 84%
“…Additionally, Gunderson et al (2001) found young women in the US Navy were more likely to have an STI than older women. While not relating to military populations, Kang et al (2014) found in a study of Australian 15-25 year olds, that being over 20 was a risk factor within this narrow sample rather than comparing this age range to older age ranges.…”
Section: Agecontrasting
confidence: 56%
See 2 more Smart Citations